Ecological Impacts of Eucalyptus tereticornis-globulus (Eucalyptus Hybrid) Plantation in a Mining Area - Abbasi, S. A.; Vinithan, S. (Indian Forester, 1999)
Environmental impact of Eucalyptus tereticornis-globulus (Eucalyptus hybrid) plantation on the undergrowth diversity, soil moisture, soil nutrients and soil organic carbon, and on wildlife has been assessed. Qualitative as well as computer-aided quantitative studies gave clear indication that the ecological impacts of Eucalyptus hybrid plantation in terms of undergrowth diversity easily matches with the performance of Acacia auriculiformis or Leucaena leucocephala monocultures and polycultures. In other aspects as well these are no different from the impacts of mono or polycultures of Leucaena leucocephala, Acacia auriculiformis, Dalbergia sissoo, and so. The authors conclude that most of the adverse environmental impacts generally alleged against Eucalypts have not been seen.